Reversible hydrogen storage from 6LiBH4–MCl3 (M = Ce, Gd) composites by in-situ formation of MH2 - Gennari, Fabiana Cristina (2011)
Different destabilized LiBH4 systems with several interacting components are being explored for hydrogen storage applications. In this study, hydrogen sorption properties of as-milled 6LiBH4–MCl3 composites (M = Ce, Gd) are investigated by X-ray diffraction, differential scanning calorimetry and thermovolumetric measurements. The chemical interaction between metal halides and LiBH4 decreases the dehydrogenation temperature in comparison with as-milled LiBH4. Hydrogen release starts at 220 °C from the decomposition of M(BH4)3 formed during milling and proceeds through destabilization of LiBH4 by in-situ formed MH2. The dehydrogenation products CeB6–LiH and GdB4–LiH can be rehydrided under moderate conditions, i.e 400 °C and 6.0 MPa of hydrogen pressure for 2 h without catalyst. A new 6LiBH4–CeCl3–3LiH composite shows promissory hydrogen storage properties via the formation by milling of CeH2+x. Our study is the first work about reversible hydrogen storage in LiBH4–MCl3 composites destabilized by in-situ formed MH2.